A corticopontine circuit for initiation of urination. (November 2018) - Yao, Jiwei; Zhang, Quanchao; Liao, Xiang; Li, Qianwei; Liang, Shanshan; Li, Xianping; Zhang, Yalun; Li, Xiangning; Wang, Haoyu; Qin, Han; Wang, Meng; Li, Jingcheng; et al.
Abstract Urination (also called micturition) is thought to be regulated by a neural network that is distributed in both subcortical and cortical regions. Previously, urination-related neurons have been identified in subcortical structures such as the pontine micturition center (also known as Barrington's nucleus). However, the origin of the descending cortical pathway and how it interfaces with this subcortical circuit to permit voluntary initiation of urination remain elusive. Here we identified a small cluster of layer 5 neurons in the primary motor cortex whose activities tightly correlate with the onset of urination in freely behaving mice and increase dramatically during territorial marking. Optogenetically activating these neurons elicits contraction of the bladder and initiates urination, through their projections to the pontine micturition center, while silencing or ablating them impairs urination and causes retention of urine. Together these results reveal a novel cortical component upstream of the pontine micturition center that is critically involved in urination. A small cluster of brainstem-projecting layer 5 neurons in primary motor cortex elicit contraction of the bladder muscle and trigger urination. These findings open new directions for treating urination-related disorders.